Respiratory Instability and Hypoxemia Episodes in Preterm Infants - Bancalari, Eduardo; Claure, Nelson (American Journal of Perinatology, 2018)
Oxygenation instability is a very common problem in the premature infant that manifests as intermittent hypoxemia episodes (HEs). These are particularly frequent in premature infants who are on mechanical ventilation beyond the first weeks after birth. However, they can also occur in spontaneously breathing infants. Some of these episodes are due to central apnea, but in ventilated infants, they are frequently due to contractions of the abdominal musculature that can splint the respiratory pump, resulting in periods of decreased lung volume and hypoventilation. HEs are often followed by periods of hyperoxemia that results from excessive oxygen supplementation given to correct the hypoxemia. These episodes increase in frequency with postnatal age and are more common in infants with chronic lung disease. Although the evidence is not conclusive, their detrimental effects on the infant's neurologic, ocular, and respiratory system may be significant. There is no specific treatment for HEs, but several interventions are available to ameliorate the severity and duration of the episodes. Further research is needed to define the impact of HEs on the preterm infant's developing central nervous system and other organ systems and to develop effective strategies to prevent these episodes.
Keywords: premature infants; episodes of hypoxemia; intermittent hypoxemia; hyperoxemia; supplemental oxygen